Parenting Training About Educating Children in the Digital Age at Gereja Utusan Pantekosta “Harvest” Madiun - Iswahyudi Iswahyudi; Bobby Kurnia Putrawan; Widjaja Sugiri (SERVIRE: Jurnal Pengabdian Kepada Masyarakat, 2022)
Gaget is a child's problem at this time and on the other hand, parents are busy with their own activities and let their children get addicted to gadgets. Thus, the purpose of this PkM is to conduct parenting training for parents about educating children. The method used is seminars. While the results of PkM are increasing parents' awareness of how gadgets affect children, and how to overcome children's addiction to gadgets and apply parenting according to the God’s Word. Gaget menjadi permasalahan anak pada saat ini dan di lain pihak, orang tua sibuk dengan kegiatannya sendiri dan membiarkan anaknya kecanduan gadget. Dengan demikian, tujuan PkM ini adalah melakukan pelatihan kepada orang tua untuk parenting tentang mendidik anak. Metode yang dilakukan adalan seminar. Sedangkan hasil PkM adalah peningkatan kesadaran orang tua apa pengaruh gadget kepada anak, serta bagaimana mengatasi kecanduan anak terhadap gadget dan menerapkan pola asuh menurut Firman Tuhan.